HISTOMORPHOMETRY OF THE THYROID GLAND IN RAT AFTER LITHIUM ADMINISTRATION - Singh, Dalvinder; Nagar, Mahindra; Prakash, Ram (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: Lithium carbonate is being used for various psychiatric and non-psychiatric illness, and has been recently observed to produce goitre and in some cases thyrotoxicosis. Most of these are based on clinical and laboratory observations. The present study was undertaken to observe the histomorphological changes in the thyroid gland after administration of lithium carbonate in rats. Methods: Adult Wistar rats (150-250 gms) were administered 40mg/kg body weight/day lithium carbonate by intraperitoneal injection for thirty days. Controls were maintained. The animals were sacrificed fifteen hours after the last injection. Thyroids were removed and processed for routine histological studies. Results: The size of the follicles were increased and showed an abundance of colloid. Statistically significant decrease in the epithelial cell size was also observed. Conclusion: The present study is probably suggestive of development of hypothyroidism after chronic administration of lithium carbonate in albino rats. So, it is advised that patients on lithium therapy should be periodically evaluated for thyroid function. Keywords: Thyroid gland, Lithium, Rat.